2014
DOI: 10.1097/01.eja.0000435015.89651.3d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laryngeal mask airway Supreme and laryngeal mask airway Pro-Seal for controlled ventilation during general anaesthesia in adult patients

Abstract: Although the single-use LMA Supreme provides lower oropharyngeal leak pressures in comparison with the LMA Pro-Seal for controlled ventilation in supine adult patients, the clinical relevance of this small difference may be debatable and should be weighed against the potential risks of transmission of communicable diseases with the LMA Pro-Seal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 25 publications
8
28
0
3
Order By: Relevance
“…Oropharyngeal leak pressure, which is one of the most important outcomes here, can vary according to the methods of measurement (e.g. palpable vs audible leak) . The use of a neuromuscular blocker may also change oropharyngeal leak pressure, but the small number of trials using these agents precluded the possibility of a subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal leak pressure, which is one of the most important outcomes here, can vary according to the methods of measurement (e.g. palpable vs audible leak) . The use of a neuromuscular blocker may also change oropharyngeal leak pressure, but the small number of trials using these agents precluded the possibility of a subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The second-generation SADs with the higher sealing pressures and tube for gastric drainage should be preferred due to their increased safety and efficacy as compared to the first-generation devices. [373839404142434445] If initial insertion of the SAD fails, changing over to another type of SAD has been shown to be successful. [46] Cricoid pressure interferes with SAD insertion by reducing the hypopharyngeal space, and therefore it should be removed.…”
Section: Optimising Endotracheal Intubationmentioning
confidence: 99%
“…Safety of any supraglottic airway device is determined mainly by its OLP and also indicates the feasibility of positive-pressure ventilation. [1314] A number of randomized clinical trials and a meta-analysis also reported that OLP between i-gel™ and LMA-S™ is similar. [678915] On the contrary to our findings, Chew et al .…”
Section: Discussionmentioning
confidence: 99%